Dogs corpses preserved with ethyl alcohol and curing salt and vacuum-packed for teaching veterinary surgery - Coelho Ferreira, Geovana (2021)
The aim of this study was to biomechanically analyze the skin of canine corpses chemically prepared with ethyl alcohol and curing salt, and vacuum packed, for the practice of veterinary surgery, in addition to obtaining the microbiological evaluation that may occur during the process. Eight canine corpses, weighing 7.96 ± 1.48 kg, were used. The animals were injected with 120 ml/kg of a solution of 20% sodium chloride, 1% nitrite and 1% sodium nitrate, and 150 ml/kg of alcohol with 5% glycerin and kept in vacuum-plastic bags at temperature between 0 and 4 °C. Skin samples were taken on day 0 (fresh samples) and on days 30, 60, 90 and 120 for biomechanical analysis, as well as for microbiological analysis of the fluids in the plastic packaging containers. The maximum rupture force presented by the control group and in the days of conservation showed that the fixation with curimg salts and the storage in vacuum packs maintained the biomechanical characteristics of the skin for up to 120 days in the corpses under refrigeration.